Contract Design with a Dominant Retailer and a Competitive Fringe - Kolay, Sreya; Shaffer, Greg (Management Science, 2013)
We show that under some conditions, quantity discounts and two-part tariffs are equivalent as mechanisms for channel coordination when an upstream firm sells its product in a downstream market that is characterized by a dominant retailer and a competitive fringe. We consider a setting in which discriminatory offers are feasible and a setting in which the same menu of options must be offered to all retailers. We find that the upstream firm's profit in both settings is independent of whether quantity discounts or two-part tariffs are used. The implication of this finding is that the firm's choice of contract design may turn on which one is easier to implement. This paper was accepted by J. Miguel Villas-Boas, marketing.